Legal Drafting in the Formulation of Local Autonomy Policies in the Education Sector in Kabupaten 50 Kota Provinsi Sumatera Barat - Afriva Khaidir; Suryanef Suryanef; Zikri Alhadi (Humanus, 2020)
Policy formulation should be essential because it will produce laws governing society and regulate the local government. Local policy position is included in the order of legislation in the Republic of Indonesia. This is where problems often occur in terms of synchronization and harmonization. Using the method of documentation study and in-depth interviews and focus group discussions, this research produces an analytical description to understand the formulation of Regional Regulations, particularly in the field of education services that, according to the 1945 Constitution, are decentralized the regions. The case study was conducted by dissecting Perda No. 6 of 2003 on Compulsory Reading and Writing of the Qur'an for School Children and Prospective Brides. The research method consists of 2 layers, the first is an inventory, and the second is a normative and procedural analysis of the process and substance of the intended public policy. The regional regulations studied were contained sharia nuances and regulated the religious sector, which was not under the authority of regional autonomy, which was derived from the principle of decentralization. In the guide, the legal drafting process in Limapuluh Kota Regency follows the applicable regulations, both with the disclosure of proposals from the DPRD and the Regional Heads by involving the leading sector SKPD in the formulation process. The Local Regulation (Ranperda) proposal has also been formatted through an Academic Paper process. However, the research found that the public policy documentation and dissemination system has not been running well and effectively.